Small and medium sized enterprises (SMEs) performance in small industrial village from perspective of creativity and online business (e-commers) - Sukardi, Sukardi; Indah, Crystal; Faturachman, Danny; Sulaeman, Karina A. (Linguistics and Culture Review, 2021)
Purpose of this research is to know and explain influence of online business/e-commerce trading and creativity on performance of small and medium-sized enterprises (SMEs) in small industry village in east Jakarta. Out of Population of 115 administrators of this industry, samples of 90 active industry/store owners are taken based on Morgan and Kreijcie table. Samples are taken based on purposive sampling. Data collection is by giving questioners. Then the data is analyzed using linier regression. The result shows that online trading and creativity affects significantly positive to performance of this industry.